Cyclic tensile strain facilitates proliferation and migration of human aortic smooth muscle cells and reduces their apoptosis via miRNA-187-3p. Issue 2 (20th December 2021) - Yang, Di; Wei, Guang-Yuan; Li, Min; Peng, Ming-Sheng; Sun, Yuan; Zhang, Yan-Liang; Lu, Chuang; Qing, Kai-Xiong; Cai, Hong-Bo
ABSTRACT: The cardiovascular is a system that contains extremely complex mechanical factors, in which the circulatory flow of blood has rich mechanical laws. Many studies have revealed that mechanical factors play a very important role in the process of revascularization. Hence, it is essential to investigate the mechanical factors in the process of revascularization in depth. A cyclic tensile strain (CTS) was applied to human aortic smooth muscle cells (HASMCs) at a frequency of 1 Hz and amplitudes of 5%, 10% and 15%, respectively. SmallRNA-seq was used to identify differentially expressed miRNAs (DE-miRNAs) responding to CTS in HASMCs. Starbase database predicted the target genes of DE-miRNAs. Metascape was applied for GO and KEGG pathway enrichment analysis and protein–protein interaction network construction. The proliferation and migration of CTS-treated HASMCs were significantly enhanced, and apoptosis were significantly reduced compared to the control group. SmallRNA-seq results demonstrated that 55, 16 and 16 DE-miRNAs were present in 5%, 10% and 15% CTS-treated HASMCs, respectively. Compared to controls, with miR-26a-2-3p and miR-187-3p being the intersection of these DE-miRNAs. Starbase database identified 189 common target genes for miR-26a-2-3p and miR-187-3p. Common target genes are mainly enriched in the basolateral plasma membrane and endocytosis. Further, in vitro experiments exhibited that CTS upregulated miR-187-3p expression, and miR-187-3p enhanced the proliferation and migration of HASMCs and reduced their apoptosis. It is suggested that miR-187-3p may be an important target for CTS participate in the process of cardiovascular disease. uf0001